The comparison of nutrient digestibility of Bligon and Kejobong goats fed king grass and peanuts straw - Hanim, Chusnul; Yusiati, Lies Mira; Budisatria, I Gede Suparta; Rachman, Fandi Widya (2016)
Bligon goats is one of goat breed which has good fertility and productivity, their population in Yogyakarta is up to 60% from total goats population and their productivity 12,000 tails per year. While Kejobong goats are another local goat breed found in Purbalingga, Central Java which has similar productivity with Bligon goats. Their population is 15,317 tails in Kejobong distric, Purbalingga, Central Java (Sodiq and Haryanto, 2007). Smallholder goat production systems are mostly based on traditional methods. This situation exists in many regions of the tropics, where goats raised in traditional systems mostly roam freely in fallow land, forest and grassland. The main feed resources of animals are native grasses, legumes that occur naturally in grass lands, tree leaves and crop residues (Osakwe and Udeogu, 2007). In Java, feed resources of goats are king grass as native grasses and peanuts straw as legumes. In wet season, those production are high in several region. The nutrient requirements of goats are determined by age, sex, breed, production system (dairy or meat), body size, climate and physiological stage. Feeding strategies should be able to meet energy, protein, mineral, and vitamin needs depending on the condition of the goats. Goats do not depend on intensive feeding systems except some supplemental feeding during growth, lactation, pregnancy and winter (Rashid, 2008). This study is designed to evaluate nutrient digestibility between bligon and Kejobong goats fed king grass and peanuts straw.